APPLICATION OF SUBJECTIVE EVALUATION FORMS IN SHAROF BOSHBEKOV S DRAMA IRON WOMAN - Imomova Ismigul Sirojiddin kizi (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In works of art, especially dramatic works, all linguistic units are involved in the realization of the writer's purpose. These language units contribute to the formation of a creative individual style, ensuring the originality of the speech of the protagonists, the vitality of the language of the work, It is active in increasing the effectiveness and sincerity. One of such means is -jon, -hon, - bek, -boy, -toy, -gina, -cha, -chok, chak, which are considered to be subjective forms of assessment, and these suffixes show all their stylistic features in the text. It is used in the context of context, not only in the sense of diminishing, but also in a number of senses, such as respect, irony, augmentation, expressiveness, expressiveness. We tried to learn these meanings on the basis of Sharof Boshbekov's drama "Iron Lady".